Length-weight relationships for five fish species caught in Keban Dam Lake, Turkey - Dartay, M.; Gul, M. R. (Hindawi Ltd, 2014)
Length-weight relationships (LWR) are presented for five commercial freshwater fish species (Luciobarbus esocinus, Heckel, 1843; Capoeta trutta, Heckel, 1843; Barbus lacerta, Heckel, 1843; Luciobarbus mystaceus, Pallas, 1814 and Capoeta umbla, Heckel, 1843) collected from Keban Dam Lake located in eastern Anatolia, Turkey. Studied samples were obtained between July and December 2008 using commercial gill nets. For each species the sample size, length range, weight range, length-weight relationships, 95% confidence intervals of a and b, coefficient of correlation and growth type are given. Values of b were between 2.915 (Luciobarbus esocinus) and 3.079 (Copoeta trutta) and r(2) values from 0.919 (Copoeta trutta) to 0.987 (Barbus lacerta) in the study. New maximum length and length-weight relationships are reported for Barbus lacerta and Luciobarbus mystaceus.